2010
DOI: 10.1203/00006450-201011001-00420
|View full text |Cite
|
Sign up to set email alerts
|

420 Fetal Growth, Preterm Birth, Neonatal Stress and Risk for Cns Tumors in Children: A Nordic Populationand Register-Based Case- Control Study

Abstract: We investigated the association between indicators of fetal growth and neonatal stress and CNS tumours diagnosed in the Denmark, Sweden, Norway and Finland in 1985-2006, using data from national cancer registries and medical birth registries. We included 3,443 children with primary CNS tumours and 16169 individually matched controls drawn randomly from the national population registries.We observed a U-shaped relation between risk for CNS tumors and birthweight, at >4.5 kg (OR 1.27; 95% CI, 1.03-1.55) and < 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…6 In addition, small size for gestational age has not been reported as a risk factor for CNS tumors, 12,13,43 although other altered fetal growth metrics have been associated with brain tumor risk. 44,45 As we observed, greater parity was previously reported to increase risk for neuroblastoma and some types of CNS tumors. 14 Associations between pediatric cancers and parity have been attributed to increased risk of infectious conditions from having older siblings, or alternatively, variation in hormone levels between first and subsequent pregnancies.…”
supporting
confidence: 69%
“…6 In addition, small size for gestational age has not been reported as a risk factor for CNS tumors, 12,13,43 although other altered fetal growth metrics have been associated with brain tumor risk. 44,45 As we observed, greater parity was previously reported to increase risk for neuroblastoma and some types of CNS tumors. 14 Associations between pediatric cancers and parity have been attributed to increased risk of infectious conditions from having older siblings, or alternatively, variation in hormone levels between first and subsequent pregnancies.…”
supporting
confidence: 69%
“…The results are statistically robust and highly unlikely to be a play of chance or bias for the following reasons: (i) we had 94 female Wilms tumor patients weighing 4 kg or more at birth, a large number comparable to the total of cases of both sexes of most previous studies, (ii) the information on birth weight was collected in compulsory and complete medical birth registries before the date of diagnosis and (iii) the observed association was due to higher birth weights in female cases and not to a chance deviation of the birth weight distribution among the control sample; comparing our Wilms tumor controls with a sample of more than 15,000 controls drawn for a study on childhood CNS tumors showed similar proportions of low and high birth weights, namely 4.5, 80.4 and 15.2% for female Wilms tumor controls of birth weights <2.5, 2.5-4 and 4 kg, respectively, and accordingly 4.5, 81.6 and 13.9% for female CNS tumor controls (both distributions including multiple births). 29 In a large United States study, the association between Wilms tumor and birth weight at 4 kg was strongest among patients with PLNR, and PLNR was slightly more common among girls (17%) than boys (9%). 7 Nevertheless, sex-specific analyses have been reported from only two studies.…”
Section: Discussionmentioning
confidence: 96%
“…29 Cases were all children with Wilms tumor (International Childhood Cancer Classification group VI(a): nephroblastoma and other nonepithelial renal tumors) 30 diagnosed before the age of 15 years. The time periods of diagnosis were January 1, 1985 to December 31, 2006 in Denmark, Norway and Sweden and during January 1, 1987 to December 31, 2006 in Finland.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, significant unmeasured confounding factors except for parental infertility may have contributed to the observed association between fertility treatment and childhood cancer in this meta-analysis. Although none of them have adequately controlled all potential confounding factors, such as age, gender, maternal age at birth, socioeconomic status, maternal smoking, low birth weight, congenital malformations, and imprinting disorders, 21,25,[47][48][49][50][51][52][53] nearly 90% of the studies (26/29 studies) included have controlled for more than one potential confounding factors. Here, 23 studies adjusted or matched for age and/or gender of children, 13 studies for maternal age at birth, 8 studies for parental socioeconomic status, 5 studies for birth order/parity, 8 studies for birthweight and gestational age, 4 studies for maternal smoking during pregnancy, and 3 studies for maternal pregnancy complication, congenital malformations or chromosomal aberrations.…”
Section: Discussionmentioning
confidence: 99%